BUSINESS FEASIBILITY ANALYSIS OF THE MSMES “SEBLAK KING” - Yurofi’ah, Ilma Alfi; Luluk Fauziah (Journal of Economic and Economic Policy, 2025)
Objective: Indonesia is one of the countries that is a tourist destination because of its culinary richness. The potential for a strong national economic base can be seen from the very large number of MSMEs and their ability to absorb a large workforce. MSME "Seblak King" is one type of culinary business that is currently popular with the public, with products made from kencur, chili, raw crackers, and various other toppings. This study aims to analyze the feasibility of the business of the MSME "Seblak King" located in Krajan Village, Purwoharjo District, Banyumas Regency, based on five aspects of feasibility, namely finance. Method: The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. Results: The results of the study indicate that the “Seblak King” business is feasible to run and develop. From the financial aspect, a positive Payback Period value is obtained, a decent Return on Investment, Net Present Value, Profitability Index and Internal Rate of Return have positive values ​​or the business is feasible to be developed and run. Based on the overall analysis, the “Seblak King” MSMES is declared feasible to run and has promising business prospects. Novelty: The feasibility of the “Seblak King” MSME business is assessed through a comprehensive approach that integrates five main aspects—namely market and marketing, technical and operational, human resources, legal, and financial—in a comprehensive and practical manner.